PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF CHILDREN’S INTERPERSONAL RELATIONSHIPS IN THE UZBEK FAMILY (Ustozlar uchun, 2026)
This article explores the pedagogical and psychological characteristics of children’s interpersonal relationships within the Uzbek family context. It emphasizes the role of the family as a primary social environment where children acquire fundamental social, emotional, and moral values. The study examines how traditional Uzbek cultural norms, such as respect for elders, care for younger family members, collective responsibility, and mutual support, influence the formation of children’s behavior and interpersonal skills.Particular attention is given to sibling relationships, including interactions between older and younger children, which serve as an important mechanism for social learning, emotional regulation, and personality development. The article analyzes key psychological processes such as emotional attachment, imitation, cooperation, competition, and empathy, highlighting their impact on children’s socialization and psychological well-being.